Ejecución presupuestaria de los gastos corrientes en el Gobierno Autónomo Descentralizado parroquial de Ricaurte. - Yánez Yarleque, Carlos Emilio (2022)
This case study was carried out in the Ricaurte Parish Gad, with the need to focus on the budgetary execution of the current expenses of this institution in the year 2021, in order to verify if the assigned amounts are correctly managed and distributed transparently. the proper use of public resources. Among the shortcomings detected, it is that the public entity does not have an established system to carry out the activities systematically, as it does not have a procedures manual that indicates each of the functions that each employee must perform, that is, that knows the resources and requirements required to perform their functions, otherwise it could cause the breach of the duties assigned to each employee of the financial department, which may result in delays in the completion of activities, delays in the delivery of processes, breach of the objectives identified by the organization in its operational plan. These findings are useful for this organization to improve its financial and administrative control and to carry out its planned activities, thus being able to provide an efficient and quality service.